Evolution of the Concepts of “Financial Architecture” and “Financial Architectonics” - Zaika Olena; Zajika O.; Заїка О. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. The development of financial markets and institutions has led to the complexity of financial systems, which in turn requires new approaches to their analysis and management. In this context, the concepts of “financial architecture” and “financial architectonics” are of particular importance. However, despite the widespread use of these terms in the scientific literature, their interpretation is often ambiguous and controversial. The purpose of the study is to examine the evolution of the essence of the concepts of “financial architecture” and “financial architectonics”, to identify their differences and interrelationships, and to formulate own definitions of these terms, taking into account modern approaches and trends in financial science. To achieve this goal, a number of theoretical methods were used, namely: monographic - for reviewing scientific publications related to the concepts of “financial architecture” and “financial architectonics”; comparative analysis - to identify the differences and common features between the concepts of “financial architecture” and “financial architectonics”, which allowed to formulate the main characteristics and relationships between these definitions; the method of systematic approach - to study the relationships between the elements of the financial system and their structuring, which allowed to consider financial architecture and financial architectonics as integrated concepts with certain characteristics and interactions; the method of historical analysis - to study the evolution of the concepts of “financial architecture” and “financial architectonics”, which allowed to trace changes in the definitions and approaches to these terms in the context of the development of financial science; the method of conceptual modeling - based on the generalization of the data obtained and the analysis of current trends in the financial sector, the author proposed her own definitions of the concepts of “financial architecture” and “financial architectonics”. Financial architecture is defined as a structured model that covers the regulation and management of financial components at the macro-, meso-, and micro-levels of the economic system, and financial architectonics is defined as a comprehensive concept that reflects the structure and interrelationships between the elements of the financial system. The distinction between these concepts allows for a deeper understanding of various aspects of financial management. Financial architectonics offers a broader view of the financial system, taking into account complex interrelationships and dynamic processes, while financial architecture focuses on specific structural components and their regulation.

Резюме. Розвиток фінансових ринків та інститутів призвів до ускладнення фінансових систем, що, в свою чергу, вимагає нових підходів до їхнього аналізу та управління. В цьому контексті поняття «фінансова архітектура» та «фінансова архітектоніка» набувають особливого значення. Однак, незважаючи на широке використання цих термінів у науковій літературі, їхнє тлумачення часто є неоднозначним і суперечливим. Метою дослідження є вивчення еволюції сутності понять «фінансова архітектура» та «фінансова архітектоніка», виявлення їх відмінностей і взаємозв’язків, а також формулювання власних визначень цих термінів з урахуванням сучасних підходів та тенденцій у фінансовій науці. Для досягнення поставленої мети використано ряд теоретичних методів, а саме: монографічний – для проведення огляду наукових публікацій, що стосуються понять «фінансова архітектура» та «фінансова архітектоніка»; порівняльний аналіз - для виявлення відмінностей і спільних рис між поняттями «фінансова архітектура» та «фінансова архітектоніка», що дозволило сформулювати основні характеристики та взаємозв’язки між цими дефініціями; метод системного підходу - для вивчення взаємозв’язків між елементами фінансової системи та їх структуризації, що дозволило розглянути фінансову архітектуру та фінансову архітектоніку як інтегровані концепції з певними характеристиками та взаємодіями; метод історичного аналізу - для дослідження еволюції понять «фінансова архітектура» та «фінансова архітектоніка», що дозволило простежити зміни у визначеннях і підходах до цих термінів у контексті розвитку фінансової науки; метод концептуального моделювання - на основі узагальнення отриманих даних та аналізу сучасних тенденцій у фінансовій сфері було запропонована власні визначення понять «фінансова архітектура» та «фінансова архітектоніка». Фінансову архітектуру визначено як структуровану модель, що охоплює регулювання та управління фінансовими компонентами на макро-, мезо- та мікрорівнях економічної системи, а фінансову архітектоніку - як комплексну концепцію, яка відображає структуру та взаємозв’язки між елементами фінансової системи. Розмежування цих понять дозволяє глибше зрозуміти різні аспекти фінансового управління. Фінансова архітектоніка пропонує ширший погляд на фінансову систему, враховуючи складні взаємозв’язки та динамічні процеси, тоді як фінансова архітектура фокусується на конкретних структурних компонентах та їх регулюванні.

A pénzügyi piacok és intézmények fejlődése a pénzügyi rendszerek bonyolultságához vezetett, ami viszont új megközelítéseket tesz szükségessé elemzésükben és kezelésükben. Ebben az összefüggésben a „pénzügyi architektúra” és a „pénzügyi architektonika” fogalma különösen fontossá válik. Annak ellenére azonban, hogy ezeket a kifejezéseket széles körben használják a tudományos irodalomban, értelmezésük gyakran kétértelmű és ellentmondásos. A tanulmány célja a "pénzügyi architektúra" és a "pénzügyi architektonika" fogalmak lényegi fejlődésének tanulmányozása, különbségeik és összefüggéseik azonosítása, valamint e fogalmak saját definícióinak megfogalmazása figyelembe véve a pénzügytudomány modern megközelítéseit és irányzatait. A cél elérése érdekében a kutatás során számos elméleti módszer került alkalmazásra, nevezetesen: monografikus - a "pénzügyi architektúra" és a "pénzügyi architektonika" fogalmakkal kapcsolatos tudományos publikációk áttekintésére; összehasonlító elemzés - a "pénzügyi architektúra " és a "pénzügyi architektonika" fogalmak közötti különbségek és közös jellemzők azonosítására, amelyek lehetővé tették a definíciók főbb jellemzőinek és összefüggéseinek megfogalmazását; a rendszerszemléletű módszer - a pénzügyi rendszer elemei és azok strukturálása közötti kapcsolatok elemzéshez, amely lehetővé tette a pénzügyi architektúra és a pénzügyi architektonika bizonyos jellemzőkkel és kölcsönhatásokkal rendelkező integrált fogalomként való felfogását; a történeti elemzés módszere - a "pénzügyi architektúra" és a "pénzügyi architektonika" fogalmak fejlődésének tanulmányozására, amely lehetővé tette e fogalmak definícióiban és megközelítéseiben bekövetkezett változások nyomon követését a pénzügyi tudomány fejlődésével összefüggésben; a fogalmi modellezés módszere - a kapott adatok általánosítása és a pénzügyi szféra modern trendjeinek elemzése alapján a cikk saját definíciókat kínál a "pénzügyi architektúra" és a "pénzügyi architektonika" fogalmakra. A pénzügyi architektúra egy strukturált modell, amely lefedi a pénzügyi összetevők szabályozását és kezelését a gazdasági rendszer makro-, mezo- és mikroszintjén, a pénzügyi architektúra pedig olyan átfogó fogalom, amely tükrözi a pénzügyi rendszer szerkezetét és elemei közötti kapcsolatokat. E fogalmak megkülönböztetése lehetővé teszi a pénzgazdálkodás különböző aspektusainak mélyebb megértését. A pénzügyi architektúra tágabb képet ad a pénzügyi rendszerről, figyelembe véve az összetett kapcsolatokat és a dinamikus folyamatokat, míg a pénzügyi architektúra konkrét strukturális összetevőkre és azok szabályozására összpontosít.
A „pénzügyi architektúra” és a „pénzügyi architektonika” fogalmak lényegének evolúciója
Еволюція сутності понять «фінансова архітектура» та «фінансова архітектоніка»
Редакційна колегія: https://aab-economics.kmf.uz.ua/aabe/about/editorialTeam
Зміст: https://aab-economics.kmf.uz.ua/aabe/issue/view/7
Keywords: financial architecture; financial architectonics; financial systems management; evolution of financial concepts; theory of financial systems